2023
DOI: 10.3389/fneur.2023.1069861
|View full text |Cite
|
Sign up to set email alerts
|

Potential association among posterior fossa bony volume and crowdedness, tonsillar hernia, syringomyelia, and CSF dynamics at the craniocervical junction in Chiari malformation type I

Abstract: ObjectiveThe characteristic morphological parameters (bony posterior fossa volume (bony-PFV), posterior fossa crowdness, cerebellar tonsillar hernia, and syringomyelia) and CSF dynamics parameters at the craniocervical junction (CVJ) in Chiari malformation type I (CMI) were measured. The potential association between these characteristic morphologies and CSF dynamics at CVJ was analyzed.MethodsA total of 46 cases of control subjects and 48 patients with CMI underwent computed tomography and phase-contrast magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…CSF hydrodynamic parameters have been increasingly recognized as a predictive factor for the surgical effect and prognosis. Previous studies have revealed that the normalization of CSF dynamic parameters was related to the improvement in clinical symptoms, and patients with greater abnormal preoperative CSF flow had a better clinical response to suboccipital decompression (14,(32)(33)(34). Fakhri et al (15) and Shaffer et al (35) showed that normalization of CSF dynamic parameters could be seen in MRI of symptomatic CM patients after operation.…”
Section: Discussionmentioning
confidence: 98%
“…CSF hydrodynamic parameters have been increasingly recognized as a predictive factor for the surgical effect and prognosis. Previous studies have revealed that the normalization of CSF dynamic parameters was related to the improvement in clinical symptoms, and patients with greater abnormal preoperative CSF flow had a better clinical response to suboccipital decompression (14,(32)(33)(34). Fakhri et al (15) and Shaffer et al (35) showed that normalization of CSF dynamic parameters could be seen in MRI of symptomatic CM patients after operation.…”
Section: Discussionmentioning
confidence: 98%